Transference and Countertransference Today. - Oelsner, Robert (Taylor & Francis, 2013)
Why has Heinrich Racker's original work on transference and countertransference proven so valuable?With a passionate concern for the field created by the meeting of analyst and patient, and an abiding interest in the central importance of transference and countertransference in analytic practice, Robert Oelsner has brought together the thought and work of seventeen eminent analysts from Europe, the United States, and Latin America. In new essays commissioned for this volume, the writers have set aside the lines that can often divide psychoanalytic groups and schoo.